183k views
4 votes
Solve the equation 3( x + 4) = 2x + 4x -6 for x

User RMu
by
4.9k points

2 Answers

1 vote

Final answer:

To solve the equation 3(x+4)=2x+4x-6 for x, simplify the equation, isolate x on one side, and solve for x.

Step-by-step explanation:

To solve the equation 3(x+4)=2x+4x-6 for x, we need to simplify the equation and isolate x on one side of the equation.

Starting with 3(x+4)=2x+4x-6, we distribute the 3 to both terms inside the parentheses to get 3x+12=2x+4x-6.

Next, we combine like terms by combining the x terms on the right side of the equation, resulting in 3x+12=6x-6.

Continuing, we can move all the x terms to one side of the equation by subtracting 3x from both sides and adding 6 to both sides. This gives us 12=3x-6.

Finally, we solve for x by adding 6 to both sides and then dividing by 3. The solution is x=6.

User Playmaker
by
5.0k points
6 votes

3(x + 4) = 2x + 4x - 6

The first step is to open the parentheses on the left by multiplying the terms inside it by the term outside. We have

3x + 12 = 2x + 4x - 6

3x + 12 = 6x - 6

Collecting like terms, we have

6x - 3x = 12 + 6

3x = 18

Dividing both sides by 3,

x = 18/3

x = 6

User GWR
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.